Prevalence of Toxoplasmosis Seropositive Antibodies among Children with Autistic Spectrum Disorders (ASD) - Omar Ibrahim, Razaw; Abdul-Kareem Khidhir Abbas (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Toxoplasma gondi is a pervasive parasite that causes a variety of diseases both in humans and animals, it infects the neural cells of the central nervous system. There have been previous reports linking this infection with Autism. Autism is a combination of complex neurodevelopmental disorders leading to alteration in social communication. This study was done to detect the frequency of seropositive Toxoplasmosis in Autistic children attending psychiatric units in Azady Teaching Hospital in Kirkuk governorate-Iraq. This case-control study was done on 40 Autistic children (30 male, 10 female) with an average age of 5.4±6 years and 40 healthy children (8 male, 32 female) with the same age range (6.1±2) year, from April 2018- January 2020. Sample collection was done by obtaining four ml of blood from all study group children for the detection of both IgM and IgG Toxoplasma gondi antibodies using the ELISA technique. Chi-square and paired T-tests were used for data analysis. The IgM serology for both Autistic and control children was negative while there was just one positive result of T.gondi IgG in Autistic Children and two positive results in normal children which made the result insignificant( X2=0.45, p-value>0.05). Regarding gender, there was no significant difference in detecting positive results between boys and girls of the study groups (X2=0.45 p value> 0.05). The study also demonstrated that Autistic Parents were statistically older than healthy children of the same age. We couldn't uncover any connection between ASD and toxoplasmosis. The age of parents & family history has a significant impact on the development of ASD.